Understanding differences in attitudes to immigration: A meta-analysis of individual-level factors - Lenka Dražanová; Jérôme Gonnot; Tobias Heidland; Finja Krüger (Kiel Institute for the World Economy (IfW Kiel), 2022)
Public attitudes toward immigration have attracted much scholarly interest and extensive empirical research in recent years. Despite a sizeable theoretical and empirical literature, no firm conclusions have been drawn regarding the factors affecting immigration opinion. We address this gap through a formal meta-analysis derived from the literature regarding immigration attitudes from the top journals of several social science disciplines in the years 2009-2019 and based on a population of 1185 estimates derived from 144 unique analyses on individual-level factors affecting attitudes to immigration. The metaanalytical findings show that two individual-level characteristics are most significantly associated with attitudes to immigration - education (positively) and age (negatively). Our results further reveal that the same individual characteristics do not necessarily explain immigration policy attitudes and attitudes towards immigrants' contribution. The findings challenge several conventional micro-level theories of attitudes to immigration. The meta-analysis can inform future research when planning the set of explanatory variables to avoid omitting key determinants.
Keywords: F22; J15; 330; meta-analysis; attitudes toward immigration; public opinion; migration; intergroup relations